Cadmium in urothelial carcinoma of the bladder - Golabek, Tomasz; Darewicz, Barbara; Kudelski, Jacek; Socha, Katarzyna; Markiewicz-Zukowska, Renata; Chlosta, Piotr; Okoń, Krzysztof; Borawska, Maria (Polish Journal of Pathology, 2014)
The aim of this study was to examine the relationship between cadmium (Cd) and bladder cancer (urothelial carcinoma of the bladder). Cadmium concentrations in two 36-sample series of bladder cancer tissue and blood, from patients with the neoplasm, were matched with those of the control group. The amount of heavy metal in every tissue sample was determined using atomic absorption spectrometry. This was correlated with tumour stage. While the median cadmium concentration levels reached statistically lower values in the bladder cancer tissue, as compared with the non-cancer one (11.695 ng/g and 56.32 ng/g respectively, p < 0.001), the median Cd levels in the blood of the patients with this carcinoma showed no statistical difference when compared to those of the control group (8.237 μg/l and 7.556 μg/l respectively, p = 0.121). The median levels of cadmium in the bladder tissue, depending on the stage of the tumour, compared with the tissue without the neoplasm, observed the same relationship for both non-muscle invasive and muscle-invasive tumours (p < 0.002 and p < 0.02 respectively). This study has shown that patients with urothelial carcinoma of the bladder had lower tissue cadmium levels than people without tumour while no difference in the Cd blood levels between the two groups of patients under investigation was found.